Empoderamiento estructural de los docentes en las instituciones públicas de educación superior en la provincia de Cotopaxi. - Montaguano Quillupangui, Evelyn Carolina (2023)
The current research has been developed since the view Institutional point, this sense, structural empowerment is a development theory oriented for people efficiently way, their different activities work, for this reason, this research has as aim to determine the teacher’s structural empowerment level into the Higher Education Public Institutions in the Cotopaxi Province. For this study, it was implemented the quantitative approach methodology, a descriptive and cross-sectional research. Previously, it was applied the structural empowerment (CWEQ-II) instrument, it developed by Laschinger, Finegan, and Shamian in 2001, which has 4 dimensions: opportunity, information, support, and resources, each with three items. Likewise, it was calculated the proportional stratified sample, it constituted 262 teachers, who formed study object part for the information collection, further, with the methodology execution, it can get the results, which allowed verifying the structural empowerment level with the teachers´ sociodemographic characteristics in the Higher Education four Public Institutions. The achieved results indicate, what a teacher´s empowerment medium and high level prevails according to the applied instrument and methodology.